2016
DOI: 10.1186/s12861-016-0142-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of gonadotropin-releasing hormone receptor 2 during the anadromous spawning migration in Coilia nasus

Abstract: BackgroundAn increase in the activity of the pituitary-gonad axis (PG-axis) and gonad development are essential for the onset of spawning migration in teleosts. In the fish Coilia nasus, gonad development and spawning migration up the Yangtze River occurs by the end of each summer. We hypothesized that gonadotropin releasing hormones receptor 2 (GnRH-R2), which together produce a signal that interacts with the PG-axis, may help to regulate spawning migration processes.ResultsIn this regard, we (1) characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition, Duan et al . () found that from May to early July, the gonadosomatic index (GSI) significantly increase during the maturation stage (stages IV and V), as the fish moves upstream to the Anqing section (620 river km) of the Yangtze River. These observations confirm that the amounts of stored lipid and protein have to be mobilised to provide energy for gonad development because anadromous grenadier anchovy do not feed during their freshwater spawning migration (Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Duan et al . () found that from May to early July, the gonadosomatic index (GSI) significantly increase during the maturation stage (stages IV and V), as the fish moves upstream to the Anqing section (620 river km) of the Yangtze River. These observations confirm that the amounts of stored lipid and protein have to be mobilised to provide energy for gonad development because anadromous grenadier anchovy do not feed during their freshwater spawning migration (Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The first GNRHR was identified in mammals in the early 1990´s (mouse, Tsutsumi et al, 1992) and a few years later the first fish Gnrhrs were described in the gilthead seabream (Pagelson and Zohar, 1992) and African catfish (Tensen et al, 1997). Since then, Gnrhrs have been characterized in many fish species (Lethimonier et al, 2004;Weltzien et al, 2004;Levavi-Sivan and Avitan, 2005;Kah et al, 2007), including the goldfish (Illing et al, 1999), Japanese eel (Okubo et al, 2000), rainbow trout (Madigou et al, 2000), striped bass (Alok et al, 2000), medaka (Okubo et al, 2001), salmon (Jodo et al, 2003), sea bass (González-Martínez et al, 2004b;Moncaut et al, 2005), fugu (Moncaut et al, 2005), spotted green pufferfish (Ikemoto and Park, 2005), cobia (Mohamed et al, 2007), zebrafish (Tello et al, 2008), Atlantic cod (Hildahl et al, 2011a,b), European eel (Peñaranda et al, 2013), Japanese grenadier anchovy (Duan et al, 2016), mackerel (Lumayno et al, 2017 and ricefield eel (Chen et al, 2018). However, the available knowledge on the distribution of Gnrhrs in cells and tissues, regulatory mechanisms and biological functions is still limited in fish.…”
Section: Structure and Types Of Gnrh Receptorsmentioning
confidence: 99%
“…However, one variant, the gnrhr2a (a Gnrhr-IIa subtype) is highly expressed in the pituitary, has significantly increased expression during the spawning season and is likely the main receptor for mediating Gnrh3 function during spawning (Hidahl 2011a(Hidahl , 2011b(Hidahl , 2013. In the clupeiforme Coilia nasus, the expression levels of a gnrhr-IIa subtype in the brain, pituitary and gonad, as well as plasma circulating levels of the Gnrhr-IIa protein, were highly correlated with migration, gonad maturation and spawning, indicating central and peripheral actions of the Gnrhr-IIa in regulating reproductive processes (Duan et al, 2016). The studies on the Gnrhr-IIb showed that the expression levels of these types of receptors are in many cases low or undetectable in the pituitary and do not correlate with reproductive processes, thus suggesting no direct actions on reproduction (Guilgur et al, 2009;Ikemoto and Park, 2005;Lin et al, 2010;Hidahl et al, 2011Hidahl et al, , 2013.…”
Section: Localization Of Gnrh Receptorsmentioning
confidence: 99%
“…Using flow drift net, required fishes were sampled by local fishermen. In short, six reach sections in the Yangtze River were selected for sampling fishes during the anadromous migration period (April to July, 2017) [31]. After fish catching, the sampled fish is dead immediately out of water.…”
Section: Methodsmentioning
confidence: 99%